Estrategias tributarias y el cumplimiento de las obligaciones de los contribuyentes de la Municipalidad Provincial de Ucayali - Contamana, 2021 - Flores Ochoa, Angela Eliana (2022)
The present research work entitled "Tax strategies and compliance with the obligations of taxpayers of the provincial municipality of Ucayali-Contamana, 2021" aiming to determine if tax strategies influence compliance with the obligations of taxpayers of the Municipality Provincial de Ucayali-Contamana, 2021. The development of the research was based on a descriptive methodology, specifying the most important characteristics and features, it was non-experimental, cross-sectional, having as a population a total of 51 people who work in the Municipality Provincial of Ucayali-Contamana, since they are directly related to the study variables. Taking as a sample the total population that collects information through a survey where 14 questions were asked with a Likert scale and six closed questions. After processing the collected data, it was possible to conclude thanks to the results that the tax strategies significantly influence the fulfillment of the obligations of the taxpayers of the Provincial Municipality of Ucayali-Contamana, 2021 since it was obtained that a Rho of Spearman, 0.837 ** and the sigma is 0.000.